CONTEXTUALIZAÇÃO DO JOGO ANTITÉTICO NO DE CONIURATIONE CATILINAE - Goettems, Miram Barcellos (Organon, 2012)
In this essay, we present an analysis on how Sallust’s antithetic thought is structured, on thesintagmatic level, in the monograph De Coniuratione Catilinae. We aim at showing that the descriptiveportraits, letters, speeches and digressions that the author interpolates along the narrative and whichbear the distinctive mark of sallustian texts (though such insertions were not original because they werea common procedure, since Herodotus, in classical historioghaphy) constitute a privileged space for thecontextualization of the dualistic theoretical model. This model that spells out several opposition pairsis presented, in a paradigmatic way, in the prologue of the monograph.